2007
DOI: 10.1103/physrevlett.98.038101
|View full text |Cite
|
Sign up to set email alerts
|

Could Humans Recognize Odor by Phonon Assisted Tunneling?

Abstract: Our sense of smell relies on sensitive, selective atomic-scale processes that are initiated when a scent molecule meets specific receptors in the nose. However, the physical mechanisms of detection are not clear. While odorant shape and size are important, experiment indicates these are insufficient. One novel proposal suggests inelastic electron tunneling from a donor to an acceptor mediated by the odorant actuates a receptor, and provides critical discrimination. We test the physical viability of this mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
219
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(226 citation statements)
references
References 30 publications
5
219
0
2
Order By: Relevance
“…32,33,59 Here, following earlier work, 24,27,29 we study a simplified model which captures the essential physics of the electron transfer process. We assume that there exist specific electronic states of the receptor that can be identified as a DA pair, with other levels well separated in energy.…”
Section: Model Of Olfactionmentioning
confidence: 99%
See 3 more Smart Citations
“…32,33,59 Here, following earlier work, 24,27,29 we study a simplified model which captures the essential physics of the electron transfer process. We assume that there exist specific electronic states of the receptor that can be identified as a DA pair, with other levels well separated in energy.…”
Section: Model Of Olfactionmentioning
confidence: 99%
“…26,30,37 It was suggested as early as 1938 that the sensing of vibrational spectra of molecules [38][39][40] -later proposed to occur via electron transfer 21,22 -could play an important role in olfaction, supplementing (rather than replacing) the existing lockand-key model. Recent work, focussing on constructing and exploring model systems that capture the important physical processes, 24,27 has shown that this is indeed a viable proposition. The suggested mechanism, which harnesses vibrationally-assisted ET in a similar manner to inelastic electron tunneling spectroscopy, 41,42 can be viewed as an example of a molecular switch, wherein specific vibrations of an external molecule actuate the receptor and lead to a pronounced electron flow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such situations appear to describe many cases of large drug molecules interacting with receptors. In the other class, the 'swipe card' (key card) picture (Brookes et al 2007), the geometric fit of the odorant with the receptor has to be good enough, but shape does not provide the information leading to actuation. An example would be Turin's proposal that selectivity arises from inelastic electron tunnelling, the receptor acting like a vibrational spectrometer, sensitive to the vibrational frequencies of the olfactant.…”
Section: Introductionmentioning
confidence: 99%